Outcomes of Cleft Palate Repair in Patients with Pierre Robin Sequence: A Matched Case-Control Study. Issue 3 (March 2016) - Hardwicke, Joseph T.; Richards, Helen; Cafferky, Louise; Underwood, Imogen; Horst, Britt ter; Slator, Rona
Abstract : Background: Pierre Robin sequence results from a cascade of events that occur during embryologic development and frequently presents with cleft palate. Some studies have shown speech outcomes to be worse in patients with Pierre Robin sequence after cleft palate repair. Methods: A cohort of Pierre Robin sequence patients who all required an airway intervention and nasogastric feeding in the neonatal period were identified and speech outcomes assessed at 5 years of age. A cleft- and sex-matched non–Pierre Robin sequence, cleft palate–only comparison group was also identified from the same institution and study period. Results: A total of 24 patients with Pierre Robin sequence that required airway and nutritional support in the neonatal period were matched for age, sex, and cleft type to a group of 24 non–Pierre Robin sequence cleft patients. There was no significant difference in the incidence of oronasal fistula between the groups. Secondary surgery for velopharyngeal incompetence was significantly more ( p = 0.017) in the Pierre Robin sequence group, who also had significantly greater nasality ( p = 0.031) and cleft speech characteristic ( p = 0.023) scores. Conclusions: The authors hypothesize that other factors may exist in Pierre Robin sequence that may lead to poor speech outcomes. The authors would suggest counseling parents of children with Pierre Robin sequence that have required a neonatal airway intervention, that speech development may be poorer than in other children with cleft palate, and that these children will have a significantly higher incidence of secondary speech surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.